Meaning no offense. The impact of anger on translation decision-making when dealing with offensive stereotypes - Naranjo, Beatriz (The Journal of Specialised Translation, 2023)
By pursuing an interdisciplinary approach between Psychology and Translation Studies, this work offers some preliminary results about the effects of anger on translation decision-making. In this study, a group of translation students were presented with two types of translation units from a blog entry in which negative judgements about people, places or situations were portrayed — potentially offensive (referred to as 'target units') and non-offensive ('distractors') ― and were instructed to choose between two translation options containing linguistic devices aimed at either attenuating or emphasizing the negative content. Their level of anger was measured using the STAXI-2 test and sentiment analysis tools. Based on cognitive and behavioural tendencies found in angry individuals, which include selective attention to anger-congruent stimuli and tendency to act against sources of threat, it was hypothesised that translators would more frequently opt for attenuated translations when they were potentially offensive in order to mitigate the threat that they may represent to them. Contrary to initial predictions, results revealed a higher number of attenuated translations for non-offensive units than for offensive ones. The role of emotion regulation, reappraisal strategies and other carry-over effects of anger in decision-making are discussed as possible factors that may explain our findings.